2014
DOI: 10.1002/ece3.1005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of a successful colonizer: isolated populations of Metrioptera roeselii regain variation at an unusually rapid rate

Abstract: Newly founded isolated populations need to overcome detrimental effects of low genetic diversity. The establishment success of a population may therefore depend on various mechanisms such as assortative mating, purging of deleterious alleles, creation of new mutations and/or repeated inflow of new genotypes to reduce the effects of inbreeding and further loss of genetic variation. We compared the level of genetic variation in introduced populations of an insect species (Metrioptera roeselii) far beyond its nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 48 publications
2
21
2
Order By: Relevance
“…conjugella analyses in the study showed a lower expected heterozygosity (He = 0.31), than was found in various insect species such as; Metrioptera roeselii "0.61" [60]; Leptomyrmex pallens "0.51" [61] and Cerambyx cerdo "0.63" [62]. However, the low expected heterozygosity was comparable to what was found in Plutella xylostella "0.35" [11], Anopheles nuneztovari (Culicidae) "0.34" [63], Glossina pallidipes "0.35" [64] and Bombus distinguendus "0.38" [65].…”
Section: Discussioncontrasting
confidence: 49%
“…conjugella analyses in the study showed a lower expected heterozygosity (He = 0.31), than was found in various insect species such as; Metrioptera roeselii "0.61" [60]; Leptomyrmex pallens "0.51" [61] and Cerambyx cerdo "0.63" [62]. However, the low expected heterozygosity was comparable to what was found in Plutella xylostella "0.35" [11], Anopheles nuneztovari (Culicidae) "0.34" [63], Glossina pallidipes "0.35" [64] and Bombus distinguendus "0.38" [65].…”
Section: Discussioncontrasting
confidence: 49%
“…A recent study conducted by Kaňuch et al (2014) confirms our findings that both allelic richness and unbiased expected heterozygosity in isolated populations are correlated with population age. The lack of evidence of recent bottlenecks in any of the sampled populations and only slightly elevated levels of homozygosity indicate that immediate consequences of founder effects are not traceable (Luikart and Cornuet 1998).…”
Section: Discussionsupporting
confidence: 93%
“…It is likely that the populations at the range margin have not reached a demographic equilibrium yet and the genetic composition is expected to change with time as a consequence of genetic drift and gene flow (Bohonak 1999). Metrioptera roeseliis ability to regain genetic diversity appears to contribute to the species successful range expansion in northern Europe (Kaňuch et al 2014;Wissmann et al 2009). …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, the ABC analysis suggested that these haplotypes likely originated from unsampled haplotypes within the eastern region of the source clade. While it is possible some of the haplotype variants could have emerged postintroduction through mutations (e.g., Agrawal & Wang, 2008; Kaňuch, Berggren, & Cassel‐Lundhagen, 2014; Vandepitte et al., 2014), such mutations would likely have added only a few new haplotypes and not likely the 74% new haplotypes we detected. With a substantial increase in sampling across the C.c.…”
Section: Discussionmentioning
confidence: 99%